Nutritional status of iron, vitamin B12, vitamin A and anemia in Mexican children: results from the Ensanut 2018-19 - Vanessa De la Cruz-Góngora; Brenda Martínez-Tapia; Teresa Shamah-Levy; Salvador Villalpando (Salud Pública de México, 2021)
Objective. To describe the current status of micronutrient deficiencies (MD) and anemia in Mexican children. Materials and methods. Serum data from 1 382 pre-school-age children (1-4 years) and 3 590 school-age children (5-11 years) Ensanut 2018-19 participants were analyzed. Iron deficiency (ID), vitamin B12 deficiency (B12D), vitamin A depletion (VADp), and anemia were identified. Logistic regression models were used to identify associations between sociodemographic characteristics of children and MD. Results. Anemia was present in 28.9 and 19.2% of the children aged 1-4 and 5-11, respectively; in ID 10 and 5.1%; B12D, in 5.1 and 4.8%, and VADp, in 4.7 and 4.3%. 18.5% of the preschool-age children and 13% of the school-age children had at least one MD associated to anemia. Conclusions. MD and anemia affect the younger children in larger proportion. Fortification and supplementation programs should be reinforced to avoid the long-term consequences of MD.